(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Urban school teachers are experiencing sedentary life style behaviors. This study was aimed to determine the prevalence of hypertension (HTN) and its relationship with associated disorders among school teachers of Dhaka city. Methods: This cross sectional study was conducted between May-October of 2017. Total 323 school teachers in Dhaka city aged between 25-59 years were enrolled using cluster random sampling technique. Data on socio-demographic profile, personal and family history, co-morbidities and blood pressure were recorded. HTN was recorded according to predefined criteria. Results: The prevalence of HTN among school teachers was 52.3%. The mean±SD age was 46.5±7.8 years. About 82% hypertensive teachers were within 41-59 years category. Majority participants were female (65.6%) and female to male ratio was 1.9:1. Female teachers were more hypertensive compared to male (54.2% vs 48.6%). Majority teachers (52%) were earning between 20,000 and 50,000 Bangladeshi Taka per month and about 61.6% had service duration>15 years. Male teachers with positive family history of diabetes mellitus (DM) were about one and half times likely to have DM as compared to negative family history (p = 0.009, OR = 1.491, 95% CI 1.138-1.954). Among hypertensive teachers, about 70% were overweight/obese and they were about 1.7 times likely to develop HTN (p=0.024, OR=1.696 and 95% CI 1.069-2.692) which was statistically significant. Conclusions: HTN is more prevalent among urban school teachers and they are at greater risk to develop HTN. Building awareness by promoting health education, healthy life style and behaviors for prevention and control of HTN should be given importance among teachers. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 70-76